Is There a Difference in the Self Efficacy of Students with Academic and Non-Academic Achievements (Sports Field)? - M. Arli Rusandi; Lisa Khairani; Elni Yakub (Bisma The Journal of Counseling, 2022)
This research was conducted to analyze the differences in the level of self-efficacy of students with academic achievements and non-academic achievements majoring in MIPA and Social Sciences. The research method used is quantitative research using survey methods. The research subjects were taken by purposive sampling technique with a sample size using the Yamane formula of 50 students with academic achievements and 38 students with non-academic achievements. The instrument used in data collection is using a self-efficacy scale. Data analysis used comparative analysis with the Independent Sample T Test. The results of the study show that: 1) The self-efficacy of students with academic achievements is in the moderate category, 2) The self-efficacy of students with non-academic achievements is in the moderate category, and 3) The results of the Independent Sample T Test, the research hypothesis is rejected. So it can be concluded that there is no difference in the self-efficacy of students who achieve academically and non-academic achievers.